ASSESSING THE IMPACTS OF NATIONAL POLICIES ON INDONESIAN AUTONOMOUS UNIVERSITIES’ RESEARCH PERFORMANCE - Rodliyah, Iis Nur; Chuang, Hsueh-Hua (Faculty of Administrative Science, Universitas Brawijaya, 2023)
This qualitative study aimed to examine the potential impact of policies granting Indonesian top universities with special autonomy status called as Legal Entity State University, or Perguruan Tinggi Negeri Badan Hukum (PTN-BH), on their research performance. This study involved an analysis of eight national policy documents related to PTN-BH or autonomous universities, which were retrieved from a trusted government regulation database webpage. All the data were collected from existing documents, making this research a document study, with data interpretation conducted through content analysis. The findings reveal that the regulations on the requirements and procedures for PTN-BH status, as well as the policy on the funding types and schemes, have contributed to the research performance disparities between universities that were granted PTN-BH status at different points in time. The updated regulations have lowered and simplified the requirements and procedures for obtaining PTN-BH status, allowing universities with lower initial performance to apply. Universities’ ability to comply with the funding policy of self-generating income, matching-fund, and performance-based funding system also influence the universities’ budgeting allocation, including for research activity. Lastly, the regulation on giving autonomy to universities in deciding their top managerial structure leading to various designations in assigning a vice-rector to manage the research affairs is also a significant factor in the university’s research performance.